Annoyance to different noise sources is associated with atrial fibrillation in the Gutenberg Health Study. (1st August 2018) - Hahad, Omar; Beutel, Manfred; Gori, Tommaso; Schulz, Andreas; Blettner, Maria; Pfeiffer, Norbert; Rostock, Thomas; Lackner, Karl; Sørensen, Mette; Prochaska, Jürgen H.; Wild, Philipp S.; Münzel, Thomas
Abstract: Background: Annoyance is a common reaction in populations exposed to environmental noise and is associated with cardiovascular diseases. We investigated for the first time the existence of an association between noise annoyance and atrial fibrillation (AF). Methods and results: Cross-sectional data from 14, 639 participants of the Gutenberg Health Study were collected between 2007 and 2012. Annoyance from road traffic, aircraft, railways, industrial/construction and neighbourhood noise during daytime and sleep were collected from all participants through questionnaires using a 5-point scale. AF was assessed via self-reported medical history and/or documentation of AF on the study electrocardiogram. 80% of the study participants were annoyed by noise to a certain degree. The major sources of annoyance during daytime and sleep were aircraft, road traffic and neighbourhood noise. We found significant associations between annoyance (per point increase) and AF for aircraft noise annoyance during daytime (odds ratio (OR) 1.04; 95% confidence interval (CI) 1.00–1.08) and during sleep (OR 1.09; 95% CI 1.05–1.13), road traffic noise annoyance during sleep (OR 1.15; 95% CI 1.08–1.22), neighbourhood noise annoyance during daytime (OR 1.14; 95% CI 1.09–1.20) and during sleep (OR 1.14; 95% CI 1.07–1.21), industrial noise annoyance during daytime (OR 1.11; 95% CI 1.04–1.18) and railway noise annoyance during sleep (OR 1.13; 95% CI 1.04–1.22). Different degrees of annoyance were not associated with changes in cardiovascular risk factors. Discussion: The results suggest for the first time that noise annoyance is associated with AF. Further studies are warranted to gain insight in the mechanisms underlying the noise-annoyance-disease relationship. Highlights: Noise-induced annoyance is common phenomenon in the general population. 84% of the persons extremely annoyed on the total annoyance scale were annoyed by aircraft noise during daytime. Noise-induced annoyance is "dose-dependently" associated with the common arrhythmia atrial fibrillation. Noise induced annoyance may represent an important cardiovascular risk factor.